Anthropocentrism: the importance of traditional oil mining in Sustainable Development - Vieronica Varbi Sununianti (Program Pascasarjana Universitas Sriwijaya, 2019)
This study shows the interaction between the natural environment and human. Starting from the revelation of the rubber price implicate on the global changes in the relationship between the physical environment with the complex social (population, technological constraints, organization, culture, and social system) at the local level. It is important to see a variation of mutual dependence and modification of social-economic changes, especially traditional oil mining (illegal). Economic interests and environmental degradation threaten the fulfillment of the next generation needs. Data collection for this study through qualitative research method with in-depth interviews as primary data and is located in the three villages (Keban 1, Macang Sakti, and Lubuk Bintialo) Musi Banyuasin District). Social inequality triggered the exploitation of natural resources widely. Local community relations with nature is very instrumental to achieve welfare. For that, need to social engineering project system that future-oriented with the collaboration of local communities, corporation, and government. But the political will to achieve sustainable development should be started by the government (state).